Evaluating the availability of gallium, indium, and tellurium from recycled photovoltaic modules - Redlinger, M.; Eggert, Roderick; Woodhouse, M. (Elsevier BV * North-Holland, 2015)
The use of thin-film copper indium gallium (di)selenide (CIGS) and cadmium-telluride (CdTe) in solar technologies has grown rapidly in recent years, leading to an increased demand for gallium, indium, and tellurium. In the coming years, recycling these elements from end-of-life photovoltaic (PV) modules may be an important part of their overall supply, but little is known about the economic feasibility and the potential quantities available. This article investigates the future role of PV recycling in supplying gallium, indium, and tellurium. The authors evaluate both the quantities available from recycling over the next century and the associated costs for recycling modules and reusing each element in PV manufacturing. The findings indicate that, in terms of technical potential, there may be significant quantities of each element available from recycling CIGS and CdTe modules. The estimated cost of recovering each element from end-of-life PV modules and reusing it in PV manufacturing is higher than current raw mineral costs; however, learning and economies of scale may reduce the reported early estimates of recycling costs. These findings help improve the understanding of recycling's role in enabling higher levels of CIGS and CdTe module production.